STK11 EXPRESSION AS A POTENTIAL PROGNOSTIC BIOMARKER IN LUNG CANCER - Bridi Loss, Lairane; Conti Filho, Carlos Elias; Grassi Ruy, Arthur; Hartwig, Suelen Mayara; Stelser Massaro, Helena; Fernandes Teixeira, Sarah (UNESC em Revista, 2025)
Lung cancer is a group of neoplastic diseases with the primary site being the lungs. For advanced lung adenocarcinoma, immunotherapy blocking PD-1/PD-L1 has become a key treatment, improving survival. However, response markers like PD-L1 expression remain imperfect. Notably, mutations in the tumor suppressor gene STK11, common in adenocarcinomas, are linked to immunosuppressive microenvironments and reduced immunotherapy efficacy. This study evaluated the relationship between STK11 expression and the prognosis of lung cancer. We analyzed "The Cancer Genome Atlas" (TCGA) database from the National Institute of Health (NIH/USA), correlating clinical and pathological data. We found that STK11 has the highest mutation frequency in lung adenocarcinoma (86.32%), primarily through substitution mutations (76.6%). The presence of this mutation is not associated with a worse prognosis. Therefore, it is concluded that further research is needed to fully understand the impact of STK11 mutations and their potential as a therapeutic response marker, as well as their association with the development of new tumor suppressor therapies. Keywords: STK11, lung cancer, biomarker, prognosis, LKB1.